THE EFFECT OF EXPERIENTIAL MARKETING AND SERVICE QUALITY ON CUSTOMER SATISFACTION WITH LOYALTY AS AN INTERVENING VARIABLE AT BENING'S CLINIC, SUNGAI PENUH CITY - Edia Satriya; Sri Fitria; Zefri Efdison (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study aims to determine how the influence of Experiential Marketing and Service Quality on Consumer Satisfaction with Loyalty as an Intervening Variable at Bening's Clinic, Sungai Penuh City, both directly and indirectly. The population in this study were all consumers who visited Bening's Clinic, Sungai Penuh City. The sample for this study amounted to 80 respondents with a technique through distributing questionnaires Based on the results of the analysis and previous discussions, the following can be concluded There is no significant positive influence between the experiential marketing variable and consumer satisfaction directly, there is a significant positive influence between the service quality variable on consumer satisfaction directly, There is a significant positive influence between the Consumer Loyalty variable on Consumer Satisfaction directly, There is a significant positive influence between the Experiential Marketing variable on Consumer Loyalty directly, there is a significant positive influence between the Service Quality variable on Consumer Loyalty directly, the direct influence is small -0.008 and the indirect influence is 0.178, it means that indirectly Experiential Marketing through Consumer Satisfaction has a significant effect on loyalty, the direct influence is 0.291 and the indirect influence is 0.273, it means that indirectly Service Quality through Consumer Satisfaction does not have a significant effect on loyalty..